Extracellular ATP-stimulated macrophages produce macrophage inflammatory protein-2 which is important for neutrophil migration - Kawamura, Hiroki (Blackwell Science Inc, 2012)
Macrophages are the major source of the chemokines macrophage inflammatory protein-2 (MIP-2) and keratinocyte-derived chemokine (KC), which play a major role in neutrophil migration to sites of inflammation. Although extracellular ATP from inflammatory tissues induces several immune responses in macrophages, it is unclear whether ATP-stimulated macrophages affect neutrophil migration. Therefore, the aim of the present study was to investigate the role of ATP-induced MIP-2 production by macrophages. When ATP was injected intraperitoneally into mice, the number of neutrophils within the peritoneal cavity markedly increased, along with the levels of MIP-2 and KC in the peritoneal lavage fluid. Consistent with this, ATP induced MIP-2 production, but not that of KC, by peritoneal exudate macrophages (PEMs) in vitro. This occurred via interactions with the P2X(7) receptor and P2Y(2) receptor. Furthermore, treatment of PEMs with ATP led to the production of reactive oxygen species. The ATP-induced MIP-2 production was inhibited by treatment with the antioxidant N-acetyl-l-cysteine. Also, MIP-2 production was inhibited by pre-incubating PEMs with inhibitors of extracellular signal-regulated kinase 1/2 or p38 mitogen-activated protein kinase. The MIP-2 neutralization reduced the increase in neutrophil numbers observed in ATP-treated mice. Taken together, these results suggest that increased production of reactive oxygen species by ATP-stimulated macrophages activates the signalling pathways that promote MIP-2 production which, in turn, induces neutrophil migration.